Giant Abscess On Serve Leprosy Reaction With Prolong Used Of Steroid - Narmada, Steven; Hasibuan, Lisa Y (Lingkar Studi Bedah Plastik Foundation, 2013)
Abstract: Leprosy patients during the course of their illness may experience the leprosy reactions, the body's immune response against Mycobacterium leprae. Long-term use of steroids for treatment may decrease the body's immune system against Mycobacterium leprae. As severe leprosy reactions, giant abscess incidence is rare and has a high morbidity and motality. Therefore, it needs a comprehensive multidisciplinary management such multiple incision and drainage, proper pharmacologic treatment for leprosy reactions as underlying disease that involves the patient's systemic condition. Patient and Method: We report one case of giant abscess in bucal, left upper and lower extremities in leprosy patients who had been taking steroids for 1.5 years due to neuritis (Paucibacillary leprosy reaction type) but the leprosy reactions became more severe and the patient's condition deteriorated. We performed multiple incision through subcutaneus and fascia to expose each compartmens of muscle and drainage to remove pus. Result: There were 2,500 cc of pus in the left femoral region and 200 cc in the left antebrachial region. The culture was negative, showing that the giant abscess was not caused by bacterial infection, but a severe leprosy reactions. Systemic complications due to leprosy reactions, the longterm use of steroids and hypoalbuminemia prevent wound healing and patient’s recovery. Summary: Long-term use of steroids in leprosy may weaken the immune system and cause a giant abscess. Therefore we need a comprehensive management of multiple surgical incision and drainage as well as medical treatment and proper nutritional support.